Program Merdeka Belajar Kampus Merdeka: Efektifkah Mewujudkan Akuntan 5.0 (Studi Kasus Pada Universitas ABC) - Angela Batara Sapa; Bertha Beloan (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
The purpose of this research is to find out whether the MBKM program can realize accounting 5.0 or not. The research method used a qualitative approach with informants from the campus and students participating in the MBKM program. Data collection through interviews. The results of the study show that it is necessary to improve the quality of human resources in facing the 5.0 era. Including for accountants who compete with current technological developments. Thus, the existence of the Merdeka Learning Campus Merdeka policy can help accounting students face and transform. This is because the freedom given to students in participating in various things can develop soft skills and hard skills. In addition, students also gain various knowledge through the experiences of the MBKM programs they participate in